Use of a cyanoacrylate ester adhesive for splinting of replanted teeth - Negri, Marcia Regina; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP]; Sonoda, Celso Koogi [UNESP]; Manfrin, Thais Mara; Vendrame dos Santos, Claudia Leticia (Blackwell Publishing, 2008)
This paper reports a case of tooth replantation in which the splinting was performed with stainless steel orthodontic wire and a widely marketed brand of quick-setting cyanoacrylate ester adhesive (Super Bonder((R))). The long-term clinical and radiographic success of the case reported in this paper indicates that the splinting technique using a quick-setting cyanoacrylate ester adhesive may be a feasible option for making a rapid, simple and efficient contention of replanted teeth in situations where the routinely used materials are not readily available.